Thermal behavior and chromatographic characterization of oil extracted from the nut of the Butia (Butia capitata) - Kobelnik, Marcelo; Fontanari, Gustavo Guadagnucci; Marques, Marcelo Rodrigues; Ribeiro, Clóvis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer Nature, 2016)
The Butia capitata (Arecaceae family) is a palm that can reach approximately from 3 feet up to 5 feet tall and is commonly found in southern Brazil. This palm produces bunches of fruit with a diameter of about 2 cm which has an acid taste and is enjoyed by many people and also wild animals such as rodents and birds. The aim of this study was to extract the oil present in butia nuts and evaluate its composition and thermal behavior. The oil was characterized by chromatography and its thermal behavior by thermogravimetry (TG) in nitrogen and oxygen atmospheres under different heating rates. The chromatographic profile of this oil reveals a predominance of saturated fatty acids. The analysis performed by thermogravimetry indicates that under oxygen atmosphere, this oil showed mass gain before the onset temperature of thermal decomposition. In nitrogen, only one mass loss was observed. The kinetic behavior showed the relationship between the uses of two sample masses, indicating the same kinetic behavior under oxygen analysis.
Keywords: Butia nut oil; Chromatographic analysis; Thermal behavior